Integrating Religiosity into the UTAUT Framework: Explaining Muslim Youth’s Intention to Adopt Digital Cash Waqf - Nuradi, Nuradi; Tanjung, Hendri; Huda, Nurul; Supriyanto, Trisiladi (PT. Riset Press International, 2026)
This research investigates the intention of Millennials and Generation Z in Indonesia to engage in digital cash waqf by integrating technology acceptance determinants with religiosity. The study adopts a quantitative research design. Data were obtained from Muslim respondents in the Millennial and Generation Z cohorts and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to examine relationships among UTAUT dimensions, religiosity, and adoption intention. The empirical findings demonstrate that performance expectancy, social influence, and facilitating conditions positively and significantly influence individuals' intention to adopt digital cash waqf. In contrast, effort expectancy does not show a statistically significant effect. Religiosity has a direct and significant impact on adoption intention and serves as a selective moderating variable, strengthening the relationship between performance expectancy and intention. By incorporating religiosity as both an explanatory and moderating factor, this study extends the UTAUT framework within the context of value-oriented Islamic philanthropy. The results suggest that digital waqf platforms should prioritize tangible benefits, robust governance, and transparency, while also leveraging religious values and social networks to enhance adoption among younger Muslim generations.